Women in Saudi secondary school EFL textbooks: a critical study of women’s empowerment as enshrined in the Saudi Vision 2030 - Alqahtani, Muneer Hezam (Frontiers in Sociology, 2024)
Since the launch of the Saudi Vision 2030, Saudi Arabia has undergone significant economic and social reforms in order to move away from the country's reliance on oil and toward a more diverse and sustainable economy. One of the important chapters in this endeavor is the empowerment of Saudi women whereby they are to be given opportunities equal to men. Against this new paradigm, this study investigates whether Vision 2030's transformative efforts surrounding women's empowerment are reflected in the country's EFL textbooks, or whether the traditional representation of Saudi women has remained unchanged. The analytical focal point is the pictorial representation of Saudi women in six textbooks which form part of the Mega Goal series, and which are used to teach English in Saudi secondary schools. The analysis examined the representations of females from three different angles: the percentage of appearances in the textbooks from the total human pictorials; the social roles and occupations depicted, and the activities that they are engaged in. Analysis along all three of these angles revealed that there is a remarkable imbalance between the depiction of men and women in these textbooks, in favour of men. The study concludes that the Mega Goal series' EFL textbooks fall short of providing a realistic representation of Saudi women and fails to include representative depictions of women who, like their male counterparts, have occupied senior roles and prestigious positions in the country. This conclusion points to the need to include such representation in EFL textbooks, so that the role of women as envisaged in Saudi's Vision 2030 complies with the Vision's determination to provide equal opportunities for both men and women.